Meningkatkan Mutu Guru Mengajar Dengan Menerapkan Pembelajaran Inovatif Model Lingkungan Sekitar Sebagai Sumber Belajar Melalui Diskusi KKG di SDN Surianeun 2 - Didi Supryadi (Universitas Mathla'ul Anwar Banten, 2017)
this Action Research aims to improve the ability of teachers to utilize the school environment as a learning resource through discussions of Teachers Working Group (KKG) SDN Surianeun 2 Patia District, Pandeglang Regency academic year 2014-2015. This reasearch also conducted improve creativity, motivation, and learning result of students and teachers. From 10 teachers who involvid, 5 teachers got score with category “good”, meanwhile 5 teacher with category “enough”. At second sycles there is a better improvement 75% teacher got score with category good with score averiage 80-89. It is accordance with the defined success criteria. In detail, the acquisition value of the average increase in teachers' ability to utilize the school environment as a learning resource. The average value of observations on the discussions is 79.38 in the first cycle to 84.88 in the second cycle. Learning scenario exercise average is 78.75 in the first cycle to 82.50 in the second cycle. learning activities or in the process of learning the average is 78.33 in the first cycle to 82.08 in the second cycle.